2016
DOI: 10.1111/lcrp.12092
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Verifiability Approach to insurance claims settings: Exploring the effect of the information protocol

Abstract: Purpose Lie detection in insurance claim settings is difficult as liars can easily incorporate deceptive statements within descriptions of otherwise truthful events. We examined whether the Verifiability Approach (VA) could be used effectively in insurance settings. According to the VA, liars avoid disclosing details that they think can be easily checked, whereas truth tellers are forthcoming with verifiable details. Method The study experimentally manipulated notifying claimants about the interviewer's intent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 34 publications
(93 reference statements)
3
80
0
Order By: Relevance
“…For example, an answer like 'I spoke to my friend James in the Vondelpark' might be a detail that could theoretically be investigated further by the interviewer (e.g., by consulting James and asking for confirmation), whereas 'I spoke to someone in the park' would not count as a verifiable detail. A series of studies showed that the number of verifiable details discriminates liars from truthtellers (Harvey, Vrij, Nahari, & Ludwig, 2016;Nahari et al, 2014a). For example, the number of verifiable details was higher in truthful insurance claims than in deceptive ones when both liars and truth-tellers were instructed to mention as much verifiable information as possible (Harvey et al, 2016).…”
Section: Verbal Deception Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an answer like 'I spoke to my friend James in the Vondelpark' might be a detail that could theoretically be investigated further by the interviewer (e.g., by consulting James and asking for confirmation), whereas 'I spoke to someone in the park' would not count as a verifiable detail. A series of studies showed that the number of verifiable details discriminates liars from truthtellers (Harvey, Vrij, Nahari, & Ludwig, 2016;Nahari et al, 2014a). For example, the number of verifiable details was higher in truthful insurance claims than in deceptive ones when both liars and truth-tellers were instructed to mention as much verifiable information as possible (Harvey et al, 2016).…”
Section: Verbal Deception Detectionmentioning
confidence: 99%
“…Because previous studies highlight the importance of asking the right questions, we used unexpected (e.g., transportation-related) questions in addition to expected (e.g., general) questions (Warmelink et al, 2012;Warmelink, Vrij, Mann, Leal, et al, 2013). Furthermore, there are indications that informing both liars and truth tellers about the quality of the expected information in truthful answers may benefit deception detection (Harvey et al, 2016;Nahari et al, 2014b, but see Nahari & Pazuelo, 2015. We, therefore, instructed half of the interviewees to provide highly specific information (e.g., names of persons or locations, dates) instead of merely asking to provide as much information as possible.…”
Section: The Current Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Across studies, this warning has resulted in an increased number of verifiable details being reported by truth tellers but not by liars, strengthening the efficiency of the Verifiability Approach. As part of the Verifiability Approach, this warning has also facilitated discrimination between truths and lies in recent insurance claims study (Harvey et al, 2017;Vrij et al, 2016). Thus, the Information protocol instructions seem to motivate truth tellers to search their memory for additional verifiable details -something that is not possible for liars to do.…”
mentioning
confidence: 99%
“…Using an 'Information Protocol', several studies (Harvey, Vrij, Nahari, & Ludwig, 2017;Nahari, Vrij, & Fisher, 2014b;Vrij et al, 2016) have examined the effect of informing participants, that the details of their statements could be subsequently checked by the interviewer. Across studies, this warning has resulted in an increased number of verifiable details being reported by truth tellers but not by liars, strengthening the efficiency of the Verifiability Approach.…”
mentioning
confidence: 99%